EXcellence Research Centre for Earth Surveillance and Space-Based Monitoring of the Environment (EXCELSIOR) for the Eastern Mediterranean Region: the establishment of EO hub for data, products and services - Hadjimitsis, Diofantos G.; Kontoes, Harry; Schreier, Gunter; Komodromos, George; Ansmann, Albert; Mamouri, Rodanthi-Elisavet; Themistocleous, Kyriacos; Michaelides, Silas; Nisantzi, Argyro; Papoutsa, Christiana; Mettas, Christodoulos; Tzouvaras, Marios; et al. (My University, 2017)
The aim of this paper is to present our vision to upgrade the existing ERATOSTHENES Research Centre established within the Cyprus University of Technology into a sustainable, viable and autonomous Centre of Excellence (CoE) for Earth Surveillance and Space-Based Monitoring of the Environment (EXCELSIOR), which will provide the highest quality of related services on the National, European and International levels. One of the goals of 'EXCELSIOR' Teaming Horizon 2020 project is to strategically position the ERATOSTHENES CoE in Cyprus, the eastern Mediterranean and Europe as an efficient knowledge hub in the fields of Earth observation, remote sensing and space technology to provide data, products and services in the above areas. Examples of ERATOSTHENES research centre will further provide Earth observation-based monitoring services and products for natural disasters and environmental applications is shown.
Keywords: ERATOSTHENES Research Centre; Earth surveillance; Space-Based Monitoring of the Environment